(untitled) (Innovaciones Educativas, 2024)
The aim of the systematization was to create a collection of cards by a group of students. These cards would serve as a didactic resource in teaching statistical or probabilistic concepts in the Costa Rican secondary education curricula. The experience involved 26 mathematics teachers in training who participated in a Didactic Statistics Course that focused on materials and resources for teaching Statistics and Probability. The task involved creating a collection of cards to be used as a didactic resource for teaching topics in these areas. Additionally, an exhibition was held to share the prepared material with the participants. This provided an opportunity to receive feedback on possible improvements in both preparation and implementation. Participants also answered a questionnaire, which aimed to gather information on challenges, opportunities, and options for improving the classroom experience. The main results indicated that these activities contribute to the development of skills and present a challenge for teachers in training. By actively engaging in the learning process, they become key participants. To facilitate a meaningful transformation of the professional work of teaching staff in Statistics, it is crucial to implement activities that will create relevant resources adapted to student contexts. This approach promotes the development of competences that foster critical thinking and problem-solving abilities.